Shopee: How Does E-commerce Affect E-consumer Perception And Satisfaction? - Khaw, Jaylene; Teoh, Joyce Kah Ting; En Loo, Kelvin Sian; Kam, Wen Jing; Fransiska, Elfi Vega (AIBPM Publisher, 2023)
Shopee was the most visited e-commerce site in Southeast Asia during the third quarter of 2021. Shopee provides hundreds of millions of consumers with a simple, convenient, secure, rapid, and satisfying online shopping experience. It is dedicated to assisting brands and sellers in achieving online shopping success, and its offerings are functional to the markets in which it operates. This study aims to examine how Shopee as an e-commerce company affects the behavior of e-consumer. We tested hypotheses using SPSS. A total of 164 Shopee users participated in an online survey via a google form. We found that perceived ease of use and trust impacted customer satisfaction. Interestingly, Â perceived price and convenience did not significantly influence customer satisfaction. This research provides new insights on e-consumers perceptions of Shopee and how this perception may promote customer satisfaction.